AIRPORT, AS A PLACE OF CONCENTRATION OF AIR TRANSPORT SERVICES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
From 1991 to 2018, there was a decrease in the number of operating airports in the Russian Federation from 1,450 to 261, that is, for 27 years, 1,189 regional airports and hubs of local airlines located in Siberia, the Far East and the Far North ceased to function. During this period, the country's air transport potential decreased by more than 4 times. Today, the state of the airport infrastructure, including fixed assets and material and technical base, i.e. federal aerodromes of civil aviation remains unsatisfactory. Including the rules for safety. Thus, the consequence of all the existing problems of the industry was the destruction of domestic air transport and air transport links, which resulted in a significant deformation of the dynamics of the development of the air transport services market.